2023
DOI: 10.3847/1538-4357/ace2bd
|View full text |Cite
|
Sign up to set email alerts
|

The Iron Yield of Core-collapse Supernovae

Ósmar Rodríguez,
Dan Maoz,
Ehud Nakar

Abstract: We present a systematic analysis of 191 stripped-envelope supernovae (SE SNe), aimed at computing their 56Ni masses from the luminosity in their radioactive tails ( M Ni tail … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 200 publications
2
3
0
Order By: Relevance
“…While 56 Ni decay can account for the late-time behavior of the light curve, an additional powering mechanism is required to explain the early-time luminosity. The inferred 56 Ni mass, kinetic energy, and ejected mass are within the distribution of values found for SNe Ic by Barbarino et al (2021) and Rodríguez et al (2023), with the ejecta mass lying toward the low end of the mass distribution. A rough order-of-magnitude estimate for the γ-ray escape time t γ and the diffusion time τ m comes from demanding an optical depth of unity for γ-ray escape, and a dynamical timescale for the diffusion of order c/v.…”
Section: Light-curve Evolutionsupporting
confidence: 78%
“…While 56 Ni decay can account for the late-time behavior of the light curve, an additional powering mechanism is required to explain the early-time luminosity. The inferred 56 Ni mass, kinetic energy, and ejected mass are within the distribution of values found for SNe Ic by Barbarino et al (2021) and Rodríguez et al (2023), with the ejecta mass lying toward the low end of the mass distribution. A rough order-of-magnitude estimate for the γ-ray escape time t γ and the diffusion time τ m comes from demanding an optical depth of unity for γ-ray escape, and a dynamical timescale for the diffusion of order c/v.…”
Section: Light-curve Evolutionsupporting
confidence: 78%
“…The theoretical correlation between 56 Ni and explosion energy has been seen before (e.g., Sukhbold et al 2016), but not in the context of such a large 3D model suite carried to, or near to, the asymptotic state. Such a correlation is also strongly suggested by observations (Rodríguez et al 2023). The intriguing correlation between explosion energy and neutron star gravitational mass is new in the detailed 3D modeling context but was anticipated in the 2D results of Nakamura et al (2015) and in the semianalytic modeling of Müller et al (2016a).…”
Section: Discussionsupporting
confidence: 57%
“…More details concerning the formalism can be found in Wang & Burrows (2024). This, too, is one of the central results of this paper, but the correlation between the two has already been anticipated theoretically (e.g., Sukhbold et al 2016) and observed astronomically (Rodríguez et al 2023). The left panel provides the 56 Ni correlation with explosion energy, with the range of predicted energies due to the fact that not all 3D models have yet asymptoted to their final values indicated.…”
Section: Ni Yields and Nucleosynthesismentioning
confidence: 74%
See 1 more Smart Citation
“…To compare the contributions of neutron-capture processes with core-collapse and Type Ia supernova yields in the bulge population, we investigate Ce and Nd abundances relative to Mg (a tracer of core-collapse supernovae, Woosley & Weaver 1995) and Mn (a pristine tracer of supernovae Type Ia, Iwamoto et al 1999;Kobayashi et al 2006). Iron is produced in supernovae Type Ia, like Mn, but presents other relevant production in core-collapse supernovae (e.g., Rodríguez et al 2023).…”
Section: Other Ce and Nd Abundance Planesmentioning
confidence: 99%